SUPERVISI MANAJERIAL DAPAT MENINGKATKAN KINERJA KEPALA PAUD TK SE-KECAMATAN RENGAT BARAT - Sunniyati, Sunniyati (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2015)
Supervision is a managerial supervision functions relating to aspects of school management is directly related to improving the efficiency and effectiveness of the school covers the planning, coordination, implementation, assessment, competence development of educational resources and other resources. In 2013 everything began to change. Supervisors in particular TK has already been placed. Supervisors tried to nurture, guide the head of the kindergarten, especially managerial administration. Gratitude that does not break the head of sub-district kindergarten Rengat West began to fix, start training, workshops both on the administrative head of the kindergarten to the curriculum development at the time. They began to guide, nurture teachers under auxiliaries. The result is the head of kindergarten in the district of West Rengat many achievements in coaching teachers both in terms of artistic creativity, innovative teaching and create APE, and also has prepared the format of supervision and enforcement. Â Kata Kunci: Supervisi Manajerial, Kepala Paud TK